Medications Adherence and Associated Factors among Patients with Type 2 Diabetes Mellitus in the Gaza Strip, Palestine - Elsous, Aymen (Front Endocrinol (Lausanne), 2017)
AIM: The aim of this study was to evaluate the adherence to anti-diabetic medications among patients with type 2 diabetes mellitus (DM) seeking medical care in the Gaza Strip, Palestine. METHODS: A cross-sectional study was conducted among 369 primary care patients with type 2 DM from October to December 2016. Adherence to medications was measured using the Morisky Medication Adherence Scale (MMAS-4). Socio-demographic and clinical variables, provider–patient relationship, health literacy, and health belief were examined for each patient. Univariate, binary logistic regression and multiple linear regression were applied to determine the independent factors influencing adherence to anti-diabetic medications using SPSS version 22. RESULTS: Of all the respondents, 214 (58%), 146 (39.5%), and nine (2.5%) had high (MMAS score = 0), medium (MMAS score = 1 + 2), and low (MMAS score ≥ 3) adherence to anti-diabetic medications, respectively. Factors that were independently associated with adherence to anti-diabetic medications were as follows: female gender [odds ratio (OR): 1.657, 95% confidence interval (CI): 1.065–2.578] and perception of disease’s severity (OR: 1.510, 95% CI: 0.410–5.560). Elderly (t = 1.345) and longer duration of DM (t = 0.899) were also predictors of adherence but showed no statistical significance (p > 0.05). CONCLUSION: The level of complete adherence to anti-diabetic medications was sub-optimal. New strategies that aim to improve patients’ adherence to their therapies are necessary taking into consideration the influencing factors and the importance of having diabetes educators in the primary care centers.